GALLERY WALK; An Alternative Learning Strategy in Increasing Students’ Active Learning - Muhammad Ridwan (Nady Al-Adab : Jurnal Bahasa Arab, 2019)
Hasanuddin University of Makassar, Indonesia, has changed its pedagogical paradigm from teaching to facilitating. The training contains strategies in managing the classroom, particularly in engaging and facilitating students in the learning process. Specifically in the Arabic language classroom, for the last 6 years. The present study outlines an action-research approach to the Gallery Walk, a practice that has proven to be successful in incorporating these strategies, to create an active-learning environment. The purpose of this classroom-based action research is to describe Gallery Walk implementation, and to analyze the effect of Gallery Walk and its modifications, in increasing students’ participation and learning. In terms of method, reflections and a questionnaire were used to collect data from 29 participating students. The questionnaire contains questions related to students’ knowledge, skills, and attitudes. The data was described and analyzed in quantitative fashion. The results show that the Gallery Walk exercise can effectively engage students in the learning process. The students can obtain knowledge effortlessly, utilize their skills in understanding the topic discussed and create a constructive attitude towards other students. The conclusion can be drawn that the four Gallery Walk sessions can significantly lead students to participate broadly in the learning process.